1990
DOI: 10.1152/ajpgi.1990.259.6.g1056
|View full text |Cite
|
Sign up to set email alerts
|

Identification and partial characterization of multiple forms of biologically active EGF in rat milk

Abstract: Milk from lactating Sprague-Dawley rats was assayed for epidermal growth factor (EGF)-like activities. A homologous radioimmunoassay (RIA) indicated the presence of immunoreactive material that competed in a nonparallel fashion with submandibular gland rat EGF (sm-r-EGF). The activity in the milk was extracted using antibodies to sm-r-EGF covalently linked to acrylamide beads. This activity was characterized by RIA, nondenaturing polyacrylamide gel electrophoresis, enzymatic digestion, radioreceptor assay, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…EGF is one of several growth factors found in breast milk, which was first characterized over three decades ago (Schaudies et al 1990). EGF is a peptide with significant interspecific structural homology (Marti et al 1989), and milk EGF is both sourced from maternal circulation and synthesized locally in mammary tissue.…”
Section: Adiponectinmentioning
confidence: 99%
“…EGF is one of several growth factors found in breast milk, which was first characterized over three decades ago (Schaudies et al 1990). EGF is a peptide with significant interspecific structural homology (Marti et al 1989), and milk EGF is both sourced from maternal circulation and synthesized locally in mammary tissue.…”
Section: Adiponectinmentioning
confidence: 99%
“…The presence of EGF-containing peptides of varying molecular masses (from 6 to 160 kDa) in urine (37,42,43) and milk (22) of different species indicates that EGF can be released (shed) from its membrane-anchored precursor. This occurs through proteolytic cleavage in the juxtamembrane region.…”
Section: Epidermal Growth Factor (Egf)mentioning
confidence: 99%
“…In order to lead to the ultimate, mature 6-kDa form of the molecule, the ectodomain needs to be further maturated in the extracellular medium. It has already been shown that, in vitro, mature EGF could be released from its precursor through the action of different type of proteases; acidic protease such as pepsin (36) or serine-proteases such as trypsin (22,39,41) and plasmin (44). Moreover, membrane fractions of both kidney (45,46) and mammary gland (47) contain a membrane-bound proteolytic activity that colocalized with pro-EGF and released soluble EGF from its membraneassociated precursor.…”
Section: Epidermal Growth Factor (Egf)mentioning
confidence: 99%
“…EGF concentrations in milk and stomach contents were measured by a modification of a radioimmunoassay published previously [38]. Anti-rat EGF antibody, purified rat EGF, and goat anti-rabbit IgG were purchased from Biomedical Technologies (Stoughton, MA).…”
Section: Egf Assaymentioning
confidence: 99%